Analisis Faktor Persepsi Manfaat dan Persepsi Hambatan Terhadap Perilaku Ibu Balita dalam Pencegahan Stunting Berdasarkan Teori Health Belief Model - Novita Eka Kusuma Wardani; Ani Media Harumi (Malahayati Nursing Journal, 2022)
ABSTRACT Stunting is a new issue that harms nutritional problems in Indonesia, affecting the child's body because it is a child's number and function. To explain the Perceived factors and Perceived Barrier related to the behavior of toddlers' mother in stunting prevention based on the theory of the Health Belief Model. This study used an observational analytic study with a cross-sectional approach. The number of samples in the study was 120 respondents using the purposive sampling technique. This research was conducted at Mojo Health Center and Mulyorejo Health Center Surabaya. The variables perceived benefits and perceived barriers have a p-value of the Wald test (Sig) 0.05, meaning that each variable has a significant partial effect on stunting prevention behavior in the model. Perceived benefits have a partial effect on stunting prevention behavior. Perceived barriers have a partial effect on stunting prevention behavior. Health workers can continue to assist the community and improve maternal and child health services in an effort to reduce stunting prevalence. The community, especially mothers with children aged 2-5 years, should design healthy and varied menus in an effort to prevent stunting in children. Keywords: Benefit, Barrier, Stunting Prevention Behavior. ABSTRAK Stunting merupakan isu baru yang berdampak buruk terhadap permasalahan gizi di Indonesia karena mempengaruhi fisik dan fungsional dari tubuh anak serta meningkatnya angka kesakitan anak. Menjelaskan pengaruh persepsi manfaat dan persepsi terhadap perilaku ibu Balita dalam pencegahan stunting berdasarkan teori Health Belief Model. Penelitian ini menggunakan penelitian analitik observasional dengan pendekatan cross sectional. Jumlah sampel dalam penelitian sejumlah 120 responden dengan Teknik simple random sampling.Penelitian ini dilakukan di Puskesmas Mojo dan Puskesmas Mulyorejo Surabaya. Variabel  Persepsi Manfaat dan Persespsi Hambatan memiliki nilai p value uji wald (Sig) 0,05, artinya masing-masing variabel mempunyai pengaruh parsial yang signifikan terhadap perilaku pencegahan stunting di dalam model.  Persepsi Manfaat dan persepsi hambatan memiliki pengaruh parsial pada perilaku pencegahan  stunting. Kata kunci: Manfaat, Hambatan, Perilaku Pencegahan Stunting.